The prevalence of right‐sided colonic diverticulosis and diverticular haemorrhage. (25th April 2013) - Faucheron, J.‐L.; Roblin, X.; Bichard, P.; Heluwaert, F.
Abstract: Aim: The study was performed to determine the prevalence of right‐sided diverticular disease in a western population and whether it is more likely to bleed than disease on the left side. Method: From January 2004 to June 2005, 796 consecutive patients were referred for total colonoscopy to 17 physicians. Data obtained included age, gender, and presence and localization of diverticula. This population was compared with a cohort of 133 consecutive patients who were admitted for colonic diverticular bleeding. Results: Three‐hundred and eighteen (40%) of the 796 patients presented with noncomplicated diverticulosis. Of these, 103 (32.4%) had right‐sided diverticula. In univariate analysis, the presence of right diverticula in patients admitted for diverticular bleeding was about twice as frequent as in patients who had diverticula with no bleeding (65.2% vs 32.4%; P = 0.0001). In multivariate analysis, the right localization of the diverticulosis was associated with a risk of bleeding, which was independent of the patients' age ( P = 0.0001, OR = 3.6). Conclusion: The prevalence of colonic diverticula increased from < 10% in adults under 40 years of age to about 75% in those over 75 years of age. Of these patients, nearly one‐third presented with right‐sided involvement. Right‐sided localization was associated with a significant risk of bleeding, which was independent of the patients' age.